2002
DOI: 10.1034/j.1600-0765.2002.00344.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characterization of bovine periodontal ligament

Abstract: This study is part of a research program that aims to develop a constitutive three-dimensional model of the periodontal ligament (PDL) through the identification of pertinent material parameters. As part of this program, bovine PDL was utilized to establish stress-strain responses under tensile and compressive loading conditions. Fresh bovine molars were secured, frozen and prepared to appropriate dimensional specifications. Bar-shaped specimens that comprised portions of dentine, PDL and bone were produced. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 41 publications
(50 reference statements)
2
68
0
2
Order By: Relevance
“…10). The highest recorded strain value of the PDL (0.5 ε) entailed the physiological deformability of the PDL structure 40) . Dissipation of energy was achieved by the bending of the overall system in which four main phenomena occurred: the spongy bone was compressed on one side and stretched on the other, the bending of the cortical bone's knife edges, the bending of the tooth, and the deformation of the PDL layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10). The highest recorded strain value of the PDL (0.5 ε) entailed the physiological deformability of the PDL structure 40) . Dissipation of energy was achieved by the bending of the overall system in which four main phenomena occurred: the spongy bone was compressed on one side and stretched on the other, the bending of the cortical bone's knife edges, the bending of the tooth, and the deformation of the PDL layer.…”
Section: Discussionmentioning
confidence: 99%
“…Although the bovine PDL is wider than human PDL, their compositions seem to be comparable 39) . In previous studies [40][41][42] , the bovine model has been considered as a promising approach to define the main parameters responsible for the mechanical behavior of human PDL.…”
Section: Materials Properties 1) Natural Tissuesmentioning
confidence: 99%
“…Bilindiği üzere periodontal ligamentin kalınlığı 0.1 ile 0.3 mm arasında değişmektedir. Bu yapı okluzal kuvvetleri absorbe etmekte ayrıca dişe gelen dış kuvvetler sonucunda periodontal lifler sıkışarak dişe önemli bir destek sağlamaktadır (3). Dişe kuvvet uygulandığı zaman başlangıçta periodontal membranın dayanımı azdır.…”
Section: Introductionunclassified
“…Periodontal ligament belirli limitlerde sıkıştırılabilir. Ayrıca bir parça elastik özelliğe de sahiptir (2,3). Çiğneme kuvveti 70 N'a kadar ulaştığı zaman, periodontal ligament 0.03-0.15 mm kadar sıkışmaktadır.…”
Section: Introductionunclassified
“…For example, van-Ruijven et al (van Ruijven et al, 2006) reported that neglecting the non-homogeneity of the alveolar bone results in important changes in stresses and strains in the model. Moreover, the mechanical response of the PDL has been reported to be non-linear and viscoelastic (Pini et al, 2002). However, not only is the model that is used to represent material important, but also the numerical values of the mechanical properties, such as Young's modulus and Poisson's ratio, are of great importance to obtain a n a c c u r a t e m o d e l .…”
Section: Materials Propertiesmentioning
confidence: 99%